Analysis of body composition parameters: Associations with gender, age, and adiposity indices in adults - Fareha Husain; Mohd. Yasir Zubair; Shahnawaz Alam (Asian Journal of Medical Sciences)
Background: Height-independent body composition parameters such as fat free mass index (FFMI) and body fat mass index (BFMI) allow height-independent interpretation of nutrition status and putatively provide a better assessment of body fat.